Pengaruh Media Pembelajaran Berbasis Unity 3D Pada Materi Tata Surya - Ni Wayan Suparmi; Ngurah Mahendra Dinatha; Maria Yuliana Kua (South Sulawesi Education Development (SSED), 2024)
The research aims to determine: 1) The average learning outcomes of the control class; 2) Average experimental class learning outcomes; 3) The difference in the average learning outcomes of the control class and the experimental class. Experimental research method, with a quasi experiment with a one group pre-test and post-test design. Sampling used purposive sampling. Data collection techniques and tools use measurement techniques in the form of learning outcomes tests. Data analysis uses descriptive and inferential analysis. The research results show: 1) The average learning outcome for the control class is 72.93 in the good category. 2) The average learning result for the experimental class was 79.87 in the very good category. 3) The difference in the average learning outcomes of the control class and the experimental class using the t-test statistical test, namely Separated Variance, obtained tcount = 5.932 and ttable = 2.064 with a significance level of 0.05. So it can be concluded that there is a difference in the average learning outcomes of the control class and the experimental class.